Lazarus Phenomenon: A Case of Spontaneous Return of Circulation After Failed Resuscitation in a Trauma Patient - Pe D Arca Barbosa, Fabio; Alicerces, Alice Alicerces; Correia, Joana Araújo; Pintassilgo, Inês; Gouveia, João; Fernandes, Antero (International Journal of Innovative Research in Medical Science, 2025)
The Lazarus phenomenon, or auto-resuscitation, refers to the spontaneous return of circulation (ROSC) after failed cardiopulmonary resuscitation (CPR). First described in 1982, it remains rare and poorly understood, with clinical and ethical implications regarding death declaration and organ donation. Proposed mechanisms include pulmonary hyperinflation, delayed drug effects, myocardial stunning, and absent reflexive brainstem activity. We present the case of a 71-year-old man admitted after cranial and thoracic trauma from a fall. He exhibited mild hypoxemia and confusion but suffered a cardiorespiratory arrest while awaiting further evaluation. CPR was initiated per Advanced Life Support (ALS) protocol. Cardiac tamponade was ruled out by bedside echocardiography. After 20 minutes of asystole with low capnography values, CPR was halted, and death was declared. Approximately one minute later, the patient spontaneously achieved ROSC but without respiratory drive. He was stabilized and transferred to the ICU. Imaging revealed subarachnoid hemorrhage, frontal bone and C7 fractures, and rib fractures, but no pneumothorax or hemothorax. Despite interventions, he ultimately died. Possible mechanisms for ROSC include relief of intrathoracic pressure, delayed drug effects, and improved cerebral perfusion after cervical collar removal. This case highlights the need for caution in declaring death and further research into auto-resuscitation.